Changing local weather and adaptation in two coastal villages in Bangladesh - Rahman, M.; Pokrant, Bob (Routledge, 2015)
Coastal Bangladesh is experiencing the effects of weather and climate-related stressors. The paper reports on the ways in which members of nine occupational groups in two coastal villages in South-west Bangladesh understand and respond differentially to recent changes in local weather and weather-related events and processes. Their understanding is grounded in local experiences and varied livelihood options, which are a complex interaction between people's social and spatial locations and local weather and non-weather events and processes. Their priorities are to protect livelihoods through resilience-building actions, which address proximate causes of vulnerability (improving coastal embankments, rehabilitating and strengthening homesteads, protecting agricultural land). Government support is limited to traditional development interventions that assist some more than others and often disconnected from local people's priorities. Most adaptation actions are practical measures within the prevailing politico-legal order. There is some evidence of more rights-based cooperative action between a national non-governmental organisation and local farmers that challenged aspects of that order.